Comparison of FEV3 and FEV3/FVC Ratio Between Smokers and Non-Smokers Who Engage in Regular Exercise - Ida Rizqa Nuraini; Nurul Widyawati; Nita Damayanti; Hartati Tuna; Ronald Aprianto Parubak; Galuh Dharanindya Ica Manohara; Dita Puspita Damayanti; Alisya Nuril Firdausi Nuzula; Ketut Suhendro (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Introduction. Smoking is a major risk factor for chronic obstructive pulmonary disease (COPD). In the early stages of disease, these pathological processes predominantly affects the small airways, known as Small Airway Disease (SAD), which is often clinically silent. FEV3 and FEV3/FVC ratio have been proposed as potential indicators of SAD. Regular exercise has been suggested to attenuate smoking-related pulmonary decline. However, evidence regarding its effect on small airway function in smokers in human studies, particularly among physically active individuals, remains limited. This study aimed to compare FEV3 and FEV3/FVC ratio between smokers and non-smokers who regularly engage in physical exercise. Methods. 30 adult male with regular exercise (18 smokers and 12 non-smokers) were included in this cross-sectional comparative study. Spirometric parameters, including percentage predicted values of Forced Expiratory Volume in three seconds (FEV3), and FEV3/FVC were measured and compared between groups using the independent samples t-test. Welch’s t-test was applied as a more robust method. Statistical analysis was computerized using Jamovi 2.3.28 software. Results. Non-smokers showed higher mean percentage predicted FEV3 and FVC compared with smokers. However, no significant differences in FEV3 (p= 0.608; effect sizes=-0.1870; 95% CI -0.911 to 0.555) and FEV3/FVC ratio (p= 0.100; effect sizes=0; 95% CI -0.487 to 0.984) between groups. Conclusion. This study found no significant differences in FEV3 or FEV3/FVC ratio between smokers and non-smokers with regular exercise. Further studies are needed to clarify the relationship between smoking, exercise, and early small airway impairment.